The Impact of Funding Liquidity on Risk-taking Behaviour of Vietnamese Banks: Approaching by Z-Score Measure - Ha, Nguyen Tran Thai; Quyen, Phan Gia (International Journal of Economics and Financial Issues, 2018)
The study analyses the impact of funding liquidity risk on risk-taking behaviour of Vietnamese commercial banks from 2002 to 2016, using the systematic GMM estimation method. The main finding is that liquidity risk (represented by deposit ratio) has a negative correlation to risk-taking behaviour (captured by Z-score. The study also examines the effects of a big bank and financial crisis on the relationship between liquidity risk and the risk-taking behaviour of banks. The results suggest that big banks will have lower risk-taking behaviour than small banks when the liquidity risk of banks is still low. However, the study cannot find the empirical statistic evidence to confirm impact of funding liquidity risk and risk-taking behaviour in during a global financial crisis. Our results are consistent with all estimation equations with or without attendance of macroeconomic factors. Keywords: Liquidity, Risk, Behaviour, Vietnamese banks, Z-score. JEL Classifications: C23, G21, G40